Enucleation of Bulbus Oculi in Domestic Cats Patients with Orbital Tumors - Ramadhan, Juliadi; Nafis S, Muhammad; Ridho Gelagar, Ario; Aulia, Usma; Zukiaturrahmah, Anna; Sukmawati, Yofa (Basic and Applied Nursing Research Journal, 2023)
The eye is an essential organ for living things, as one of the five senses of the eye is very vulnerable to infectious or non-infectious diseases. The orbital tumor is one of the disorders in the cat's eye that can attack the eye muscles, nerves, and lacrimal glands. This study aims to diagnose and treat the enucleation of bulbus oculi in domestic cats and patients with orbital tumors. This activity was carried out at the Veterinary Practice "Drh. Juliadi Ramadhan, M.Si." Jl. Payakumbuh-Lintau No. 12 Regency 50 City, West Sumatra Province. The results showed that one of the treatments for orbital tumor cases can be done by enucleation of the oculi bulk. This operation uses a subconjunctival method to remove the eye, the nictitating membrane, and a little eyelid by minimizing the removal of extraocular muscle tissue. After surgery, intense treatment is carried out by maintaining the sanitation of the cage and administering anti-inflammatory drugs, antibiotics, and vitamins.